Sabellaria jeramae, a new species (Annelida: Polychaeta: Sabellariidae) from the shallow waters of Malaysia, with a note on the ecological traits of reefs - Nishi, Eijiroh; Matsuo, Kanako; Capa, Maria; Tomioka, Shinri; Kajihara, Hiroshi; Kupriyanova, Elena K.; Polgar, Gianluca (Zootaxa, 2015)
A new species of the genus Sabellaria Lamarck, 1818 (Annelida: Polychaeta: Sabellariidae) is described from the intertidal zone of Jeram, Selangor, Malaysia. Sabellaria jeramae n. sp. is a gregarious species that constructs large reefs several hundreds of meters long and 50–200 m wide. The new species is distinguished from other congeners by the character combination of the presence of a single kind of middle paleae with conspicuous morphology, and outer paleae with long frayed teeth. Morphological features of the species are described and compared to those of all congeneric species. We also compare the reef structure and geographical distribution of the new species to those of the members of the family Sabellariidae around the world, demonstrating the ecological traits of the reefs.